Comparing effects: a reanalysis of two studies on season of birth bias in anorexia nervosa. Issue 1 (December 2017) - Winje, Eirin; Torgalsbøen, Anne-Kari; Brunborg, Cathrine; Stedal, Kristin
Abstract Background Outcomes from studies on season of birth bias in eating disorders have been inconsistent. This inconsistency has been explained by differences in methodologies resulting in different types of effect sizes. The aim of the current study was to facilitate comparison by using the same methodology on samples from two studies with differing conclusions. Methods The statistical analyses used in each study were applied to the samples from the other study and the resulting effect sizes, Cramêr's V and odds ratio (OR), were compared and discussed. Results For both studies, the Cramêr's Vs ranged between 0.03 and 0.08 and the OR ranged between 0.85 and 1.31. According to common conventions, Cramêr's Vs below 0.10 and ORs below 1.44 are considered small. Conclusion As a marker of one or more potential risk factors, the observed effects are considered to be small. When reanalysed allowing for direct comparisons, studies with contrasting conclusions converge towards an absence of support for a season of birth bias for patients with AN.